Training to use a commercial brain-computer interface as access technology: a case study. - Taherian, Sarvnaz; Selitskiy, Dmitry; Pau, James; Davies, T. Claire; Owens, R. Glynn (Disability & Rehabilitation: Assistive Technology, 2016)
Purpose: This case study describes how an individual with spastic quadriplegic cerebral palsy was trained over a period of four weeks to use a commercial electroencephalography (EEG)-based brain-computer interface (BCI).Method: The participant spent three sessions exploring the system, and seven sessions playing a game focused on EEG feedback training of left and right arm motor imagery and a customised, training game paradigm was employed.Results: The participant showed improvement in the production of two distinct EEG patterns. The participant’s performance was influenced by motivation, fatigue and concentration. Six weeks post-training the participant could still control the BCI and used this to type a sentence using an augmentative and alternative communication application on a wirelessly linked device.Conclusions: The results from this case study highlight the importance of creating a dynamic, relevant and engaging training environment for BCIs.Implications for RehabilitationCustomising a training paradigm to suit the users’ interests can influence adherence to assistive technology training.Mood, fatigue, physical illness and motivation influence the usability of a brain-computer interface.Commercial brain-computer interfaces, which require little set up time, may be used as access technology for individuals with severe disabilities